P2r – A Pairwise Testing Strategy Supporting Execution Resumption - Helal, Mohammed H.S. (2013)
Achieving an accepted level of software product quality assurance requires exhaustive and time consuming testing process, especially when testing software with large number of parameters and large number of possible input values for its parameters. Pairwise software testing have been commonly employed since it proved its usefulness to sample lists of test cases for such software while achieving an accepted level of code line and function coverage. However this process might require hours even days, since reducing the size of the produced list require time consuming computations. In case interruption occurred while generating test suite (e.g. due to power failure, hardware or software malfunctions), the process must be restarted from the beginning, much time and effort will be wasted if process have been interrupted when it’s near completion. In order to address the aforementioned issue, a number checkpointing schemes have been studied to refer the most suitable scheme to match pairwise test suite strategy. The project focuses on the development of a new pairwise strategy P2R, which can generate sufficiently competitive pairwise test suites in terms of test suite size and execution time. In order to achieve this target, P2R employed a new checkpointing scheme that is based on an amalgam of periodic and dynamic checkpointing schemes. Experiments have proven that P2R provides the ability to resume existing test while generating competitive results.